An optimized high-quality DNA isolation protocol for spodoptera frugiperda J. E. smith (Lepidoptera: Noctuidae) - Marín L., Diana Victoria; Castillo, Diana Katherine; López Lavalle, Luis Augusto Becerra; Rodríguez Chalarca, Jairo; Pérez, Cristo Rafael (Elsevier, 2021)
An optimized high-quality DNA isolation protocol was developed using body segment tissue from the Fall Armyworm (Spodoptera frugiperda), that will allow documenting genetic variability based on biotypes, facilitating studies on the appearance, distribution and population dynamics of the fall armyworm at the molecular level. The resulting protocol is an easy-to-use, timesaving method that can rapidly achieve high quality, high-yielding total genomic DNA, using chemicals and everyday consumables available in a molecular laboratory. This new method of DNA extraction avoids the contamination of polysaccharides, salts, phenols, proteins and other cellular by-products that can interfere with subsequent reactions. DNA purity estimates reveal A260: A280 ratios greater than 1.9, which were evidenced by quality test on agarose gel, observing complete integrity and high purity of the resulting samples, and yielded 30–99 µg/g of total DNA. Therefore, the quality of the DNA produced from this extraction is suitable for subsequent molecular applications: (i) next generation whole genome sequencing, (ii) conventional polymerase chain reaction for genotyping, (iii) barcodes and (iv) gene cloning.